Ethos, pathos, and logos in research article introductions: Persuasive rhetorical practices across research paradigms - M. Affandi Arianto; Jufrizal; Maulluddul Haq; Rifki Oktoviandry; Dewi Syafrina (Studies in English Language and Education, 2026)
The introduction of a research article (RA) is pivotal in conveying the study’s value. While authors must effectively communicate the study’s implications and contributions, little attention has been paid to the persuasive strategies they use to achieve this goal. This study investigates persuasive rhetorical strategies in research article (RA) introductions, specifically comparing how international and novice Indonesian authors present their research values across qualitative, quantitative, and mixed-method paradigms. The analysis encompasses 120 applied linguistics RAs and employs a two-pronged methodological approach. First, we analyzed the frequency of occurrence of the promotional step using Swales’ (2004) CARS model. Second, we applied El-Dakhs et al.’s (2024) modified framework of persuasive rhetorical strategies, built upon Dontcheva-Navratilova et al.’s (2020) model of persuasion. Our findings reveal distinct patterns in how international and novice Indonesian authors employed promotional strategies in their RA introductions. These patterns manifest both in their use of promotional steps and their deployment of specific rhetorical strategies. Based on these findings, we provide pedagogical implications for academic writing tutors in optimizing authors’ promotion and offer practical guidelines for novice authors on writing more effective, convincing, and impressive RA introductions, with particular emphasis on persuasive rhetorical strategies to enhance the presentation of research values.